Life Events and Subjective Well-being: The Case of Having Children - Peder J. Pedersen; Torben Dall Schmidt (Institute for the Study of Labor (IZA), 2014)
The literature on Happiness and Subjective Well-Being (SWB) has been dominated by studies of the impact from income and labour market status - and the impact on happiness from changes in these determinants. It seems obvious to expect an impact from non-economic factors as well. In the present paper we focus on the eventual impact on SWB from having children. The dominant result in the rather few studies until now is the finding of no or even a negative impact on subjective well being following birth of a child. We focus on the impact from having children using two very big panel data sets. The first is the European Community Household Panel (ECHP) with data collected over 8 annual waves from 1994 to 2001 in 15 EU member countries. Observations are available for up to 15 countries with big differences in fertility levels, child care institutions and labour force participation for married women. At the same time, the ECHP data contains a lot of relevant demographic and labour market background variables to be included in the econometric analyses of the SWB impact from children. The second data set is The German Socio Economic Panel (GSOEP). Like the ECHP, the GSOEP data contains many relevant background factors. This presents a unique opportunity to combine the cross country perspective in the ECHP data with the possibility presented by the GSOEP of following the impact from giving birth over a significantly longer period including approximately 11.000 households.
Keywords: D1; I31; J13; 330; subjective well-being; life events; panel data